Clinical Use of Diuretics in Heart Failure, Cirrhosis, and Nephrotic Syndrome - Qavi, Ahmed Hassaan; Kamal, Rida; Schrier, Robert W. (International Journal of Nephrology, 2015)
Diuretics play significant role in pharmacology and treatment options in medicine. This paper aims to review and evaluate the clinical use of diuretics in conditions that lead to fluid overload in the body such as cardiac failure, cirrhosis, and nephrotic syndrome. To know the principles of treatment it is essential to understand the underlying pathophysiological mechanisms that cause the need of diuresis in the human body. Various classes of diuretics exist, each having a unique mode of action. A systemic approach for management is recommended based on the current guidelines, starting from thiazides and proceeding to loop diuretics. The first condition for discussion in the paper is cardiac failure. Treatment of ascites in liver cirrhosis with spironolactone as the primary agent is highlighted with further therapeutic options. Lastly, management choices for nephrotic syndrome are discussed and recommended beginning from basic sodium restriction to combined diuretic therapies. Major side effects are discussed.